Windsor Group (Late Mississippian) stratigraphy, Magdalen Islands, Quebec: a rare eastern Canadian record of late Visean basaltic volcanism - Giles, Peter (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2008)
ABSTRACT The Magdalen Islands archipelago is the single site in the north-central Gulf of St. Lawrence where surface exposures of the Windsor Group, an important Mississippian (Visean) marine marker interval within the thick Late Devonian-Early Permian fill of the Maritimes Basin, permit stratigraphic comparison with the type Windsor Group and the correlative Codroy Group of western Newfoundland. The presence of volcanic rocks associated with regionally more typical marine carbonate rocks, evaporites, and fine-grained redbeds make this local Windsor Group succession unique in eastern Canada. The volcanic rocks, including vesicular and amygdaloidal basalts with minor pyroclastic rocks, are interstratified in surface exposures with middle Windsor Group gypsum, limestone, and siltstone of late Asbian age. Similar sedimentary suites higher in the Windsor Group, assigned biostratigraphically to the Brigantian and questionably the earliest Pendleian substages, lack any associated volcanic rocks (Île Boudreau) or are in tectonic contact with volcanic-bearing middle Windsor Group successions (Île d’Entreé). The Cap au Diable Formation, erected as a volcanic-dominated rock unit of the upper Windsor Group on the Magdalen Islands, is here abandoned. Thick salt deposits lacking intercalated carbonate rocks, which underlie and are presumed to have diapirically intruded middle and upper Windsor Group strata, are believed to represent the product of the first major cycle of Mississippian marine sedimentation in the region. The Magdalen Islands Windsor Group succession, except for its regionally unique volcanic component, is most comparable to that of south-central and eastern Nova Scotia in its overall character. This tectonically dismembered remnant of an apparently complete succession contrasts with rocks of similar age in southeastern New Brunswick and northwestern Nova Scotia which lack upper Windsor Group marine carbonate members and contain only a limited number of middle Windsor Group marine carbonate bands.